(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
SARS Coronavirus-2 (SARS-CoV-2) pandemic has shown a devastating effect worldwide. More than 1.62 million people have lost their life due to this dangerous virus and it has become one of the major concerns worldwide. It has become an emerging global issue concerning different scientific communities. Here an attempt has been made to develop a vaccine against the SARS-CoV-2 virus using epitope-based subunit vaccines and reverse vaccinology and immunoinformatics methods. With the help of computational experimentations and multi-epitope-based drug designing studies, we have successfully designed 5 different vaccine structures which were further analyzed for insilco toxicity as well as molecular interaction studies. Significant interacting candidates were further subjected to insilco immuno simulation for the data point of about a year time. This work could provide new hope for development of effective vaccine in the face of global threat arising from the emerging virus.